2014
DOI: 10.1002/hlca.201300234
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpenoids from the Fruits of Alpinia oxyphylla and Their Anti‐Acetylcholinesterase Activity

Abstract: Fourteen sesquiterpenoids were isolated from the fruits of Alpinia oxyphylla Miq. Their structures were elucidated based on NMR analyses (1H, 13C, DEPT, 1H,1H‐COSY, HMQC, HMBC, and NOESY) and identified as 12‐nornootkaton‐6‐en‐11‐one (3), (+)‐(3S,4aS,5R)‐2,3,4,4a,5,6‐hexahydro‐3‐isopropenyl‐4a,5‐dimethyl‐1,7‐naphthoquinone (5), nootkatene (6), 9β‐hydroxynootkatone (7), 2β‐hydroxy‐δ‐cadinol (8), 4‐isopropyl‐6‐methyl‐1‐tetralone (11), oxyphyllone E (12), oxyphyllone D (13), oxyphyllanene B (15), oxyphyllone A (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The oxidized sesquiterpenes obtained in this study have been shown to exhibit antiproliferative( compound 3) [47] and NO-synthesis-inhibiting (compounds 3 and 11)a bilities. [45][46] The products 7-10 are structurally close to the acetylcholinesterase-inhibiting agent 24 [28] and, therefore, likely to show similar properties. The oxidized sesquiterpenes can serve as precursors for compound libraries for the improvemento ft hese pharmaceutically interesting properties.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The oxidized sesquiterpenes obtained in this study have been shown to exhibit antiproliferative( compound 3) [47] and NO-synthesis-inhibiting (compounds 3 and 11)a bilities. [45][46] The products 7-10 are structurally close to the acetylcholinesterase-inhibiting agent 24 [28] and, therefore, likely to show similar properties. The oxidized sesquiterpenes can serve as precursors for compound libraries for the improvemento ft hese pharmaceutically interesting properties.…”
Section: Resultsmentioning
confidence: 98%
“…[47] The oxidized zerumbone (6)p roducts 7-10 are structurally close to (9E)-humulene-2,3;6,7-diepoxide( < Scheme 3, 24), ap romisinga nti-acetylcholinesterase agent for the treatment of Alzheimer's disease. [28] Compounds 7-10 could thusbetested for similarfunctions. Generally,the introduction of functional groupsbyP 450s paves the way for further derivatizations.…”
Section: Applications Of the Oxidized Sesquiterpene Productsmentioning
confidence: 99%
“…Compared with LPS-treated cells, preincubation with 12 suppressed LPS-induced expression of TLR-4, iNOS, and cyclooxygenase-2 (COX-2) and reduced the p-NF-κB/NF-κB ratio (Figure ). Compound 12 was previously reported in phytochemical studies on grapefruit juice and the fruits of Alpinia oxyphylla . ,, This compound inhibited LPS-induced NO production and protected against oxidative stress-induced adipose-derived mesenchymal stem cells. , A possible mechanism of action has not been proposed. In the present study, Western blotting and molecular docking indicated that compound 12 exerted anti-neuroinflammatory activity probably via regulation of TLR-4/NF-κB signaling, and so it has the potential to be developed as a possible therapeutic agent to treat NDDs.…”
Section: Resultsmentioning
confidence: 99%
“…It has been used as traditional medicine for the treatment of nephrotic syndrome, ulceration, dementia, and intestinal disorders for more than a thousand years [ 1 ]. Pharmacological and phytochemical investigations of A. oxyphylla have led to the identification of a variety of biologically active components including fruit oil, flavonoids, sesquiterpenes, diarylheptanoids, and phenolic compounds [ 2 , 3 ]. Among them, diarylheptanoids have been identified as a major class of characteristic constituents in A .…”
Section: Introductionmentioning
confidence: 99%